A randomized, double-blind study comparing the efficacy and safety of trazodone once-a-day and venlafaxine extended-release for the treatment of patients with major depressive disorder. (May 2020) - Fagiolini, Andrea; Albert, Umberto; Ferrando, Laura; Herman, Erik; Muntean, Cosmina; Pálová, Eva; Cattaneo, Agnese; Comandini, Alessandro; Di Dato, Giorgio; Di Loreto, Giorgio; Olivieri, Luisa; Salvatori, Enrica; et al.
Abstract : This double-blind, randomized study evaluated the efficacy and safety of trazodone OAD (once-a-day) in comparison with venlafaxine XR (extended-release) in 324 patients (166 trazodone and 158 venlafaxine) with major depressive disorder (MDD). The primary efficacy endpoint was the mean change from baseline in the 17-item Hamilton Depression Rating Scale (HAM-D) at week 8. Both treatments were effective in reducing the HAM-D-17 total score at week 8 vs. baseline (intent-to-treat: trazodone –12.9, venlafaxine –14.7; per protocol: trazodone –15.4, venlafaxine –16.4). Patients in the venlafaxine group achieved better results after 8 weeks, whereas the trazodone group achieved a statistically significant reduction in HAM-D-17 following only 7 days of treatment. The most frequent adverse events (AEs) were dizziness and somnolence in the trazodone group, and nausea and headache in the venlafaxine group. Most AEs were mild-to-moderate in severity. This study confirmed that both venlafaxine XR and trazodone OAD may represent a valid treatment option for patients with MDD. Abstract : Supplemental Digital Content is available in the text.